2015
DOI: 10.1186/s12934-015-0318-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic expression program of Saccharomyces cerevisiae along a mixed-culture wine fermentation with Hanseniaspora guilliermondii

Abstract: BackgroundThe introduction of yeast starter cultures consisting in a blend of Saccharomyces cerevisiae and non-Saccharomyces yeast strains is emerging for production of wines with improved complexity of flavor. The rational use of this approach is, however, dependent on knowing the impact that co-inoculation has in the physiology of S. cerevisiae. In this work the transcriptome of S.cerevisiae was monitored throughout a wine fermentation, carried out in single culture or in a consortium with Hanseniasporaguill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 80 publications
8
50
0
Order By: Relevance
“…Gene RRI2 is a subunit of the COP9 signalosome complex, which plays a role in the mating pheromone response (Maytal-Kivity et al 2002, Wee et al 2002. Similar results were reported by Barbosa et al (2015), where yeast with a higher fermentative activity could result in the increased expression of genes related to fermentation stress response. Such induced ESR genes could be due to a higher activity of yeast in the fermentation with added BCAAs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Gene RRI2 is a subunit of the COP9 signalosome complex, which plays a role in the mating pheromone response (Maytal-Kivity et al 2002, Wee et al 2002. Similar results were reported by Barbosa et al (2015), where yeast with a higher fermentative activity could result in the increased expression of genes related to fermentation stress response. Such induced ESR genes could be due to a higher activity of yeast in the fermentation with added BCAAs.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with the results of this study. In addition, PDC5 encoding decarboxylases and AAD3, AAD4, AAD14, ADH2 encoding dehydrogenases were up-regulated in response to addition of BCAAs, which could facilitate yeast to metabolise BCAAs and produce more higher alcohols (Marks et al 2003, Barbosa et al 2015. The expression of GAP1 is controlled by nitrogen catabolite repression (NCR) (Magasanik and Kaiser 2002), which is strongly repressed when there is yeast-preferred N (such as ammonium and glutamine) in the medium, but is depressed in a medium containing only low N (such as proline) or when cells are starved for N (McCusker and Haber 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Lage et al [22] have observed the same effect using a co-culture of H. guilliermondii and the same commercial strain of S. cerevisiae used herein. Later, Barbosa et al [79] showed that the presence of the non-Saccharomyces strain of H. guilliermondii had an evident regulatory control of S. cerevisiae genes that impact H 2 S liberation during wine fermentation [86][87][88]. In this line, we could only speculate that Mp39 could have a similar effect on the transcriptome of S. cerevisiae.…”
Section: S Cerevisiae and M Pulcherrima Single And Mixed Fermentationsmentioning
confidence: 83%
“…The isolate Mp39 was selected to conduct fermentations, either in single-or in mixed-culture with the commercial strain S. cerevisiae UCD522, based on the high tolerance to ethanol and SO 2 levels (up to 9% (v/v) and 2 mM, respectively), the good growth performance in GJM 267 , high β-glycosidase, β-lyase and protease activities, and low ability to produce H 2 S. Given the known effect of nitrogen availability on S. cerevisiae performance during alcoholic fermentation either in single [47,52,77,78] or in mixed-culture with non-Saccharomyces yeast [22,79], the fermentation trials were conducted under two different nitrogen regimes.…”
Section: S Cerevisiae and M Pulcherrima Single And Mixed Fermentationsmentioning
confidence: 99%
“…For ensuring complete alcoholic fermentation mixed inoculations of selected strains of these species with S. cerevisiae are usually employed . Hence, inoculating mixed cultures of yeasts generating quality aromas has been revealed as an interesting tool in the wine industry for limiting the potential uniformity of aromatic characteristics of final wine and gaining in sensory complexity …”
Section: Introductionmentioning
confidence: 99%